2015
DOI: 10.1139/tcsme-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Surface Stress Effects on the Dynamic Behavior of Actuated Non-Classical Nano-Bridges

Abstract: The influence of surface stress and small scale on the dynamic pull-in behavior of nano-bridges is investigated in this paper. For this purpose, the governing equation of motion is derived based on the modified couple stress theory and Homotopy Perturbation Method with an auxiliary term is employed to produce the approximate solution of nano-beam vibrations. The effects of actuation voltage, initial conditions, surface energy and length scale parameter on the pull-in instability and fundamental frequency of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Previously, this theory was employed in different NEMS/MESM structures [42][43][44][45][46]. Effects of the surface excess energy (i.e., surface energy and surface stress) on the mechanics of ultra-thin films have been investigated via atomistic [47][48][49] and continuum [50][51][52][53][54][55][56][57] models. These studies demonstrated that the effects of the surface excess energy increase with the decrease in the film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, this theory was employed in different NEMS/MESM structures [42][43][44][45][46]. Effects of the surface excess energy (i.e., surface energy and surface stress) on the mechanics of ultra-thin films have been investigated via atomistic [47][48][49] and continuum [50][51][52][53][54][55][56][57] models. These studies demonstrated that the effects of the surface excess energy increase with the decrease in the film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…This size e ect cannot be modeled by classic continuum mechanics. In order to overcome this shortcoming, the non-classical theories, such as nonlocal elasticity [35], Couple Stress Theory (CST) [36][37][38], strain gradient theory [39], modi ed couple stress theory [40], etc., have been developed to consider the size e ect on theoretical continuum models. Despite other size-dependent theories, limited research has been conducted on modeling the ultra-small structures using the CST [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…They have derived Pasternak medium force and Winkler spring force in their Studies. Surface stress and small scale effects on the dynamic pull-in behavior of nano-bridges were investigated using modified couple stress theory and homotopy perturbation method by Sedighi [23]. The effects of surface stress lead to more remarkable and accurate solutions for various nano-scale mechanical analyses; therefore, more efficient analyses can be obtained, considering these effects, especially by existence of in-plane forces [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%